2001
DOI: 10.1097/00001756-200110290-00024
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and non-steroidal anti-inflammatory drugs inhibit amyloid-β aggregation

Abstract: The neurotoxic and proinflammatory actions of the Alzheimer peptide amyloid-beta (Abeta) are dependent on its aggregation and beta-sheet conformation. Chronic use of non-steroidal anti-inflammatory drugs (NSAIDs) such as aspirin for arthritis decreases the risk of developing Alzheimer's disease (AD) by unknown mechanisms. We report that these drugs inhibit human Abeta aggregation in vitro and reverse the beta-sheet conformation of preformed fibrils at clinically relevant doses. Aspirin prevented enhanced Abeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 26 publications
5
83
0
1
Order By: Relevance
“…3B) by decreasing tyrosyl radicals in COX-2. Alternatively, this inhibitory effect of NSAIDs may be a consequence of the direct interactions of NSAIDs with A␤ peptide that have been described (49,50). The concentrations of indomethacin and ibuprofen used in this study are similar to those in the report by Weggen et al (50), who demonstrated that some NSAIDs decrease the production of human A␤1-42.…”
Section: Cox-2 Cross-links A␤supporting
confidence: 81%
“…3B) by decreasing tyrosyl radicals in COX-2. Alternatively, this inhibitory effect of NSAIDs may be a consequence of the direct interactions of NSAIDs with A␤ peptide that have been described (49,50). The concentrations of indomethacin and ibuprofen used in this study are similar to those in the report by Weggen et al (50), who demonstrated that some NSAIDs decrease the production of human A␤1-42.…”
Section: Cox-2 Cross-links A␤supporting
confidence: 81%
“…Moreover, these NSAIDs dose-dependently destabilized preformed fAßs. Thomas et al (2001) suggested that the anti-aggregation effect of NSAIDs may be due to their interaction with epitope 3-6 and/or 25-35 in Aß, which are considered crucial to Aß aggregation and neurotoxicity. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, except the preliminary study where Thomas et al (2001) used the non-physiological short peptide , the effects of NSAIDs on the formation and destabilization of Alzheimer's ß-amyloid fibrils (fAß) in vitro have not been studied in detail.…”
mentioning
confidence: 99%
“…Thus, reducing the level of Ab in the brain and inhibiting the aggregation of Ab are promising strategies for AD therapy [2]. Various compounds such as peptides [3,4], antioxidants [5,6], anti-inflammatory drugs [7], and antibodies [8,9] have been reported to have inhibitory effects on the aggregation of Ab. Furthermore, antibodies against Ab reduce the level of the protein in the brain of APP transgenic mice and inhibit neurotoxicity [10].…”
Section: Introductionmentioning
confidence: 99%